The risk of bleeding and encephalopathy in surgical patients with liver cirrhosis - Petrișor Banu; Salvatore Settineri; Emanuele Maria Merlo; Maria Rosaria Anna Muscatello; Nicolae Bacalbașa; Carolina Negrei; Bianca Gălățeanu; Octav Ghinghină; Ioana Păunica; Cristian Bălălău (Journal of Mind and Medical Sciences)
Liver cirrhosis is a disease with an increasing incidence. Surgical procedures in patients with cirrhosis are also increasing, due to a longer life expectancy in these patients and also to the improvement of therapeutic and diagnostic resources. Digestive hemorrhage in the cirrhotic patient requires emergency medical intervention (intensive therapy, endoscopic or even surgical approaches), being at the same time a factor that precipitates episodes of encephalopathy, i.e. the conventional complication of cirrhosis. Hepatic encephalopathy represents one of the most severe clinical events of cirrhosis, being associated with high morbidity and mortality. The causes of hepatic encephalopathy are briefly presented in this paper. Therapeutic approaches currently available consist in the administration of non-absorbable disaccharides such as lactulose and non-absorbable antibiotics such as rifaximin. New therapeutic perspectives are under evaluation, e.g. ammonia scavengers and the modulation of gut microbiota. Clotting disorders in patients with liver cirrhosis are more severe as the disease progresses and involves complex mechanisms, as presented in this review. The correction of possible disorders of hemostasis should be promptly made as a sine qua non condition prior to surgery.